2021
DOI: 10.20956/bioma.v7i1.18093
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Lahan Dan Komposisi Jenis Tanaman Penyusun Agroforestry Di Kecamatan Sesean Kabupaten Toraja Utara

Abstract: Agroforestry system recently developed by the community to meet their needs. But many people’s don’t understand yet to select suitability plants on the agroforestry land. This study aims to determine the land characteristics and components of agroforestry in District Sesean, Toraja District. This research caried out in the way comparethe requireiment of plants and charactristic at land. Plants in research location are robusta coffee, cocoa, banana, mangosteen, buangin (pine mountain), aren, bamboo betung, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…At acidic pH, fungi are generally more dominant than bacteria and actinomycetes [11]. The results of [12] research found that the pH of the soil under a Swietenia macrophylla stand in Sa'dan Matallo Village, Sa'dan District, North Toraja Regency was 6.18 (including slightly acidic criteria). Differences in the location where it grows and possibly in climate will affect soil pH from one place to another.…”
Section: Soil Chemical Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…At acidic pH, fungi are generally more dominant than bacteria and actinomycetes [11]. The results of [12] research found that the pH of the soil under a Swietenia macrophylla stand in Sa'dan Matallo Village, Sa'dan District, North Toraja Regency was 6.18 (including slightly acidic criteria). Differences in the location where it grows and possibly in climate will affect soil pH from one place to another.…”
Section: Soil Chemical Propertiesmentioning
confidence: 95%
“…The presence of trees in the study area maintains the presence of organic matter in the soil [13]. Meanwhile [12] found that the organic matter content under Swietenia macrophylla stands in Sa'dan Matollu Village, North Toraja Regency was 1.40 (classified as low criteria). The organic matter content of a soil is affected by the presence of litter on the soil surface.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Sistem agroforestri adalah salah satu upaya konservasi sistem pertanian ke arah usaha tani terpadu, sehingga dapat tercapai optimalisasi lahan, dimana pepohonan ditanam secara tumpang sari dengan satu atau lebih spesies tanaman semusim. Menurut Rachmat (2022), agroforestri pada prinsipnya dioptimalkan untuk memecahkan masalahan pemanfaatan lahan dan pengembangan pedesaan serta mengoptimalkan potensi dan peluang yang ada untuk kesejahteraan manusia dengan adanya kelestarian sumber daya beserta lingkungannya. Salah satu agroforestri di Jawa Tengah berada di Desa Gemawang, Kecamatan Ngadirojo, Kabupaten Wonogiri, Jawa Tengah yang komoditas utamanya merupakan pohon jambu mete (Anacardium occidentale L.).…”
Section: Pendahuluanunclassified
“…Genus Hibiscus merupakan tumbuhan yang memiliki prospek pengembangan yang baik, karena memiliki nilai ekonomi yang tinggi dan potensi pasar yang terbuka lebar, misalnya tanaman yang berfungsi sebagai hiasan seperti Bunga Sepatu (H. rosa-sinensis), Bunga Sharon (H. syriacus), Waru Landak (H. mutabilis), dan Bunga Okra (H. moscheutos). Sementara itu, Rosella (H. sabdariffa) dapat dikonsumsi sebagai bahan minuman atau makanan, serta Kenaf (H. cannabinus) dapat dimanfaatkan sebagai bahan dalam membuat serat (Lihiang et al, 2022).…”
Section: Pendahuluanunclassified